Self-Regulated Learning and Academic Performance in Chilean University Students in Virtual Mode During the Pandemic: Effect of the 4Planning App - Jaramillo, Andrés; Salinas-Cerda, Juan Pablo; Fuentes, Paula (Frontiers in Psychology, 2022)
Research on the use of smartphone apps with the aim of developing self-regulated learning (SRL) and increasing academic performance of university students in virtual mode, as a result of the COVID-19 pandemic, is recent and scarce. The present article shows the results of a study that analyzed the effect of using the 4Planning app with an intracurricular approach on SRL and on the academic performance of 119 first-year psychology students in virtual mode, at a Chilean university (MAge = 22.81, SDAge = 6.52). The research was conducted with quantitative methodology and a quasi-experimental design, with pre- and post-test measurements of an experimental group and comparisons with three control groups. The results show that students who used the app during ten weeks of the first academic semester 2021: (1) increased SRL self-report, (2) increased academic self-efficacy and, (3) obtained higher academic performance, compared to those who did not use it. The above occurs because the 4Planning app activates functions of the self-regulatory system of goal-directed behavior, which allows exercising the capacity of self-direction and self-influence on this type of behavior in the particular context of academic performance, which produces SRL. It is concluded that the 4Planning app is effective in developing self-regulation and improving the academic performance of first-year university students, in virtual learning mode.